Studying Saudi English as a New Variety: A Multi-variate Analysis - Duddu, Prudhvi Raju; Ghani, Muhammad Usman (Journal of Education Culture and Society, 2022)
Aim. This multi-dimensional analysis explores prominent lexico-grammatical features in English used in the Kingdom of Saudi Arabia (KSA). The research focuses on the linguistic variation in editorials in Saudi English newspapers. The study’s goals were to create a specialised corpus of Saudi English, to determine how Saudi English differs from British English, and to establish Saudi English as an independent form of English, allowing syllabi designers to serve ESP course developers better. Method. Douglas Biber’s multi-dimensional analysis (2006), a corpus-based, quantitative, empirical, and comparative technique for studying linguistic variety, was used by the researchers for analysing this language diversity. Quantitative and functional techniques were employed in the research. The authors examined and statistically analysed the acquired data to establish the communicative function of press editorials. Biber’s (2006) tagger was used to tag the data. Then, using the analysis of variance (ANOVA), the linguistic differences between Saudi publications and British newspapers were determined. Results. The results indicate that Saudi Newspaper Editorial (SNE) is more informational, explicit, abstract, and less argumentative than British Newspaper Editorial (BNE). On one dimension, SNE produces non-narrative while BNE produces narrative discourse. Except for D2, the findings of the internal comparison reveal that there are minor variations in the mean score of Saudi newspaper editorials. Saudi Gazette creates a non-narrative discourse on D2, whilst Arab News produces a narrative one. Cognitive value. The findings support the claim that English spoken in Saudi Arabia qualifies as a distinct variation of English.